# If r(x) = 3x – 1 and s(x) = 2x + 1, which expression is equivalent to r/s (6)?

Functions are the backbone of calculus and algebra. Let's see how using in this problem.

## Answer: If r(x) = 3x – 1 and s(x) = 2x + 1, r/s (6) is equivalent to 17/13.

Let's understand the solution in detail.

**Explanation:**

In this problem, first we perform the division operation on the given functions and find r(x) / s(x).

Hence, r(x) / s(x) = (3x - 1) / (2x + 1).

Now, to find r/s (6), we substitute x = 6 in the above equation.

Hence, r(6) / s(6) = r/s (6) = (3(6) - 1) / (2(6) + 1) = 17/13.